Even a Previous Light-Active Physical Activity at Work Still Reduces Late Myocardial Infarction and Stroke in Retired Adults Aged>65 Years by 32%: The PROOF Cohort Study - Hupin, David; Raffin, Jérémy; Barth, Nathalie; Berger, Mathieu; Garet, Martin; Stampone, Kevin; Celle, Sébastien; Pichot, Vincent; Bongue, Bienvenu; Barthelemy, Jean-Claude; Roche, Frédéric (Frontiers in Public Health, 2019)
Background: Work may contribute significantly to daily physical activity (PA) and sedentary behaviour (SB). Physical inactivity and SB at work might be two major risk factors for premature morbidity. Therefore, the aim of this research was to describe self-reported past PA and SB at work and during leisure time within the PROOF cohort subjects, and to determine consequences of PA and SB on late health of these now retired workers. Material and methods: The PROOF cohort study was used to prospectively allow assessment of the predictive value of PA and SB at work and during leisure time among a healthy retired French population, with regard to cardiovascular and cerebrovascular events. PA (MET-h/week) and SB (h/d) were assessed using the Population Physical Activity Questionnaire (POPAQ) and the Global Physical Activity Questionnaire (GPAQ). Odds ratios (ORs with 95% CIs) for cardiovascular and cerebrovascular events were associated with each level of PA at work: light (<3 MET), moderate (3-5.9 MET), vigorous (≥6 MET) and were compared to SB at work. Results: Out of the 1011 65-year-old subjects initially included, the 15-year follow-up has been currently completed for 688 (68%) subjects; 89 deaths (all-cause mortality, 9%) and 91 fatal and nonfatal cardiovascular and cerebrovascular events (9%), were reported. An active work (light, moderate or vigorous intensity) was associated with a 21% reduced risk of cardiovascular (myocardial infarction) and cerebrovascular events (stroke) (OR=0.79, 95% CI: 0.32-0.91, p<0.02) compared to sedentary work. This relationship was already significant for light intensity work (32%; i.e., OR=0.68, 95% CI: 0.31-0.87, p<0.02). Conclusion: There is strong causal evidence linking PA and SB at work with late cardiovascular and cerebrovascular disease. All in all, the risk for onset of myocardial infarction and stroke was lower among those who had a previous active work compared to those with previous sedentary work. Even previous light active work produced substantial health benefits.